2014
DOI: 10.1111/acem.12520
|View full text |Cite
|
Sign up to set email alerts
|

Future Directions in Sex- and Gender-specific Emergency Medicine

Abstract: The 2014 Academic Emergency Medicine consensus conference “Gender-Specific Research in Emergency Medicine: Investigate, Understand, and Translate How Gender Affects Patient Outcomes” convened a diverse group of stakeholders to target gaps in emergency medicine (EM) sex- and gender-specific research and identify research priorities. At the close of the conference, the executive committee sought feedback from group leaders and conference attendees about the next critical steps in EM sex- and gender-specific rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…Over the past 20 years, concerted efforts have been made to identify health disparities based on gender, race, and ethnicity . Additionally, the specialty of emergency medicine has sought to define the key priorities in gender‐based research with respect to chest pain and ischemic heart disease among other disparities . However, despite these and other focused efforts like Healthy People 2010, it has been reported that these disparities still persist .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past 20 years, concerted efforts have been made to identify health disparities based on gender, race, and ethnicity . Additionally, the specialty of emergency medicine has sought to define the key priorities in gender‐based research with respect to chest pain and ischemic heart disease among other disparities . However, despite these and other focused efforts like Healthy People 2010, it has been reported that these disparities still persist .…”
Section: Discussionmentioning
confidence: 99%
“…19 Additionally, the specialty of emergency medicine has sought to define the key priorities in gender-based research with respect to chest pain and ischemic heart disease among other disparities. 8,9,20 However, despite these and other focused efforts like Healthy People 2010, it has been reported that these disparities still persist. 21 Our study sought to determine if these patterns of racial and gender disparities were present in a large cohort of prospectively evaluated chest pain patients presenting to four EDs (two in North Carolina; one in Boston, Massachusetts; one in Jackson, Mississippi) with a heterogeneous population of patients and diverse practice patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Conference participants identified lack of funding or inability to access funding as the most common barrier to implementation of this research agenda. 2 We assembled a diverse group of funders (both federal and non-federal; AA, JB, RC, RF, JS) to serve on a panel to discuss the future of sex- and gender-specific research and training opportunities for emergency care researchers. The moderators were two of the conference organizers (BS, EKC).…”
Section: Introductionmentioning
confidence: 99%